2006
DOI: 10.1088/0022-3727/39/9/028
|View full text |Cite
|
Sign up to set email alerts
|

Thermal resistance and compressive strain of underwater aerogel–syntactic foam hybrid insulation at atmospheric and elevated hydrostatic pressure

Abstract: The purpose of this study was to present a new underwater thermal insulation designed for flexibility and high thermal resistance. The insulation was a hybrid composite of two constituents: syntactic foam and an insulating aerogel blanket. Methods for treating and combining the constituents into a hybrid insulation of several designs are presented. A final configuration was selected based on high thermal resistance and was tested for thermal resistance and compressive strain to a pressure of 1.2 MPa (107 msw, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…They are extremely light and have very high internal surface areas. These materials consist of three-dimensional silica networks with pores of nanometer dimensions, and are expected to show a huge increase in their applications due to their excellent thermal and acoustic insulation properties. , However, the structure of aerogels has very low compressive strength and high susceptibility toward fracture. In order to overcome this problem while maintaining the isolation properties of the materials, we developed polymer nanoparticles with a core of low glass transition temperature ( T g ) and a shell containing groups that can be covalently attached to the porous silica structure during the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…They are extremely light and have very high internal surface areas. These materials consist of three-dimensional silica networks with pores of nanometer dimensions, and are expected to show a huge increase in their applications due to their excellent thermal and acoustic insulation properties. , However, the structure of aerogels has very low compressive strength and high susceptibility toward fracture. In order to overcome this problem while maintaining the isolation properties of the materials, we developed polymer nanoparticles with a core of low glass transition temperature ( T g ) and a shell containing groups that can be covalently attached to the porous silica structure during the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 These include catalysis, optics, electronics, sensors, coatings, biochemistry, medicine, and others. [6][7][8][9][10][11][12][13] A promising field to sol-gel hybrid inorganic-organic materials, namely, the silica-based ones, is thermal-acoustic insulation. Indeed, silica aerogels are known for their unique properties in this field: they are nonflammable, extremely light (densities in the range 3-500 kg‚m -3 ), and excellent thermal and acoustic insulators (thermal conductivity in the range 0.01-0.02 W m -1 K -1 and acoustic impedance between 103 and 106 kg‚m -2 ‚s -1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The sol−gel process has emerged as the most successful method to synthesize hybrid organic−inorganic composites since the mild conditions involved in this soft chemistry process are ideal for avoiding damage to the organic components. The variety of inorganic and organic precursors available, as well as the multiplicity of strategies to the synthesis of hybrid sol−gel materials, broaden the range of structures and properties achievable and allow an impressive number of possible applications. , These include catalysis, optics, electronics, sensors, coatings, biochemistry, medicine, and others. …”
Section: Introductionmentioning
confidence: 99%
“…New materials were developed to construct the immersion suit as well. Bardy et al [40] compared the thermal resistance of a suit fabricated from aerogel-syntactic foam hybrid insulation with that of a foam neoprene suit [40]. It was concluded that unless the surface depressions were eliminated, foam neoprene provided more thermal protection.…”
Section: Shell Fabrics Of Immersion Suitsmentioning
confidence: 99%